Molecular Profiling of Noncoding Mutations Distinguishes Nevoid Melanomas From Mitotically Active Nevi in Pregnancy. (March 2020) - Jackett, Louise A.; Colebatch, Andrew J.; Rawson, Robert V.; Ferguson, Peter M.; Thompson, John F.; McCarthy, Stanley W.; Wilmott, James S.; Scolyer, Richard A.
Abstract : The accurate recognition of subtle melanomas and their distinction from benign mimics is an oft-recurring diagnostic problem, critical for patient management. Melanomas that bear resemblance to benign nevi (so-called nevoid melanomas, NMs) and benign mitotically active nevi in pregnancy (MANP) are 2 lesions particularly prone to error. Molecular data, including analysis of noncoding regions, in MANP and NM are very limited. This study sought to identify differences in clinical, pathologic, and molecular characteristics between MANP and NMs to facilitate correct diagnosis and reduce the risk of overtreatment or undertreatment. Clinicopathologic characteristics of NM (n=18) and MANP (n=30) were evaluated, and mutation data were analyzed using next-generation sequencing for available cases in each group (NM, n=8; MANP, n=12). All MANP showed innocent histopathologic characteristics apart from increased mitotic activity, frequently in both superficial and deep parts of the lesion (median dermal mitotic rate: 2/mm 2, range: 1 to 7/mm 2 ). All cases of NM demonstrated a characteristic nevoid silhouette, subtle atypical architectural and cytologic features, and variable mitoses (median mitotic rate: 3/mm 2, range: 1 to 5/mm 2 ). Median NM tumor thickness was 1.4 mm. Four of 10 NM patients with follow-up had metastatic disease, including 3 patients who developed widespread metastases, with 1 disease-related death. No other recurrences have been identified (follow-up period: 24 to 60 mo). None of the 15 MANP patients with available follow-up had a recurrence. Most NMs harbored hotspot mutations in NRAS (6/8, 75%). Noncoding mutations were significantly more common in NMs than in MANP (median: 4 vs. 0, P =0.0014). Copy number alterations were infrequent but, when present, were seen in NMs (3/8 NMs vs. 0/12 MANP). All NMs but only 1 of 12 MANP had >1 abnormality in the noncoding regions. Similar to conventional common acquired nevi, MANP mostly harbored driver BRAF mutations, while activating NRAS mutations, noncoding mutations, and copy number alterations were rare. NM and MANP have subtle but recognizable distinguishing histopathologic characteristics that are underpinned by molecular differences. Mutation analysis of targeted noncoding mutations may assist in the diagnosis of difficult lesions.